Fabrication of ZnO–GO hybrid for enhancement of chemically bonded phosphate ceramic coatings corrosion protection performance on AISI304L stainless steel. Issue 6 (14th July 2020) - Tang, Hao; Liu, Yaxuan; Bian, Da; Guo, Yongxin; Zhao, Yongwu
Abstract: In this paper, a solvothermal method is used to prepare nano‐sized zinc oxide‐graphene oxide (ZnO–GO) hybrid, and the ZnO–GO hybrid is characterized by X‐ray diffraction analysis, Raman, Fourier transform infrared spectroscopy, and scanning electron microscopy. In addition, chemically bonded phosphate ceramics coatings with different content of ZnO–GO hybrid are prepared on the stainless steel through the sol‐gel method. The corrosion performance of the coatings is evaluated by electrochemical properties and the analysis of the surface and cross morphology of the coating. Results indicate ZnO–GO hybrid significantly enhances the compactness and corrosive behavior of the coating because the overlapping structure of GO flake improves the barrier performance of the coating. Besides, ZnO nanoparticles on the surface of GO can react with aluminum dihydrogen phosphate binder, in that case the adhesion between GO and the coating is improved.